SIMULATION OF IMAGING EXTRASOLAR PLANETS NEARBYSTAR - Jallod, Uday; Mohammed, A. (Iraqi Journal of Science, 2024)
Two-dimensional computer simulations are carried out to demonstrate theessential features of observing extrasolar planet nearby star. It has been shown thatthe wings of the point spread function of the optical telescope play an important rulein suppressing the features that related to the planet. The planet lies beneath thesewings and the final image that recorded by an optical telescope looks like a star.Quantitative assessment of observing planet nearby star at different relativebrightness and separation are demonstrated in this study.